2012
DOI: 10.1200/jco.2012.30.15_suppl.602
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant bevacizumab (B) and trastuzumab (T) in combination with weekly paclitaxel (P) as neoadjuvant treatment in HER2-positive breast cancer: Results from a phase II trial (AVANTHER).

Abstract: 602 Background: B in combination with T has showed meaningful activity in patients (pts) with metastatic HER2-positive breast cancer. AVANTHER is a Phase II trial of preoperative systemic therapy combining B with T and P in a weekly regimen in HER2 positive breast cancer to assess safety and efficacy of the combination. Methods: Pts with centrally-confirmed HER2-positive (IHC 3+ or FISH positive) breast cancer (stage II or III including locally advanced) received neoadjuvant chemotherapy (NC) with weekly P (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A single-arm phase II study of sunitinib, docetaxel, and trastuzumab in HER2positive MBC reported 16 PRs in 22 patients [107]. In the phase II AVANTHER study of neoadjuvant bevacizumab (Avastin; Genentech), a monoclonal anti-VEGF antibody, with trastuzumab and paclitaxel, pCR was achieved in 18 of 44 HER2-positive patients [108]. Another phase II study is evaluating neoadjuvant trastuzumab and chemotherapy with or without bevacizumab (NCT01367028).…”
Section: Other Targetsmentioning
confidence: 99%
“…A single-arm phase II study of sunitinib, docetaxel, and trastuzumab in HER2positive MBC reported 16 PRs in 22 patients [107]. In the phase II AVANTHER study of neoadjuvant bevacizumab (Avastin; Genentech), a monoclonal anti-VEGF antibody, with trastuzumab and paclitaxel, pCR was achieved in 18 of 44 HER2-positive patients [108]. Another phase II study is evaluating neoadjuvant trastuzumab and chemotherapy with or without bevacizumab (NCT01367028).…”
Section: Other Targetsmentioning
confidence: 99%